Insult to Injury? Women and Mental Disorder in Italian Photography and Visual Culture - Hill, Sarah P. (Violence against women, 2023)
This article shows how representations of women labeled as mentally ill in photography in Italy have been framed and marked by forms of violence, and how they continue to shape perceptions of women. It argues that the Italian case is a particularly interesting and revealing one, and that such images need to be viewed in the context of the shared status of photography and psychiatry as contemporarily “modern” inventions that have played important roles in reinforcing or contesting violent and institutionalized systems of surveillance and oppression of women.